2014
DOI: 10.5435/jaaos-22-01-29
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytokines in Posttraumatic Arthritis

Abstract: The development of arthritis after joint injury is commonly known as posttraumatic arthritis (PTA). The inciting traumatic event may range from cartilage contusion and bone bruise combined with meniscus or ligament tear, to intra-articular fracture. End-stage PTA is often indistinguishable from primary osteoarthritis. However, knowing the time of the inciting traumatic event in a patient with PTA provides an opportunity to understand the events following joint injury that lead to the progression of arthritis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 43 publications
0
58
1
3
Order By: Relevance
“…[25][26][27] To this end, data from animal studies and early clinical trials suggest that early inhibition of the intra-articular (IA) inflammatory response (e.g., 4 weeks) and posttraumatic injury of the knee may improve clinical outcomes. 28 Morisset et al reported an improvement in cartilage repair following IA injection of an adenoviral vector carrying an IL-1ra gene, 29 indicating that modulation of the joint's chemical environment may be beneficial for chondrocyte and tissue health. 30 Palliative strategies for managing joint pain include antiinflammatory analgesics such as nonsteroidal anti-inflammatory drugs alongside IA injections of glucocorticoids or hyaluronan.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] To this end, data from animal studies and early clinical trials suggest that early inhibition of the intra-articular (IA) inflammatory response (e.g., 4 weeks) and posttraumatic injury of the knee may improve clinical outcomes. 28 Morisset et al reported an improvement in cartilage repair following IA injection of an adenoviral vector carrying an IL-1ra gene, 29 indicating that modulation of the joint's chemical environment may be beneficial for chondrocyte and tissue health. 30 Palliative strategies for managing joint pain include antiinflammatory analgesics such as nonsteroidal anti-inflammatory drugs alongside IA injections of glucocorticoids or hyaluronan.…”
Section: Introductionmentioning
confidence: 99%
“…Despite improvements in surgical management of articular injuries, the incidence of posttraumatic OA has remained relatively unchanged over the last several decades [36]. Although the exact mechanism(s) that lead to development of posttraumatic OA remain unknown, there has been increased interest in the role of the postinjury inflammatory response leading to chondrocyte apoptosis and synovitis [32,36].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported levels of Interleukin 1 and TNF-α to have reached their climax 24 hours after injury (Hui et al, 2012;Lieberthal et al, 2015). These levels remain high for weeks and even months after trauma (Catterall et al, 2010;Olson et al, 2014;Christiansen et al, 2015). Based on clinical observations, cartilage derived biomarkers increase significantly a month after knee injury (Kramer et al, 2011;Konttinen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%